No Difference in Mortality and Outcomes After Addition of a Nearby Pediatric Trauma Center. Issue 12 (17th December 2022) - Naaseh, Ariana; Grigorian, Areg; Lekawa, Michael; Dolich, Matthew; Schubl, Sebastian; Joe, Victor; Nahmias, Jeffry
Abstract : Objectives: Previous studies demonstrate that higher volume pediatric trauma centers (PTCs) offer improved outcomes. This study evaluated pediatric trauma volume and outcomes at an existing level I (L-I) adult and level II (L-II) PTC after the addition of a new children's hospital L-II PTC within a 2-mile radius, hypothesizing no difference in mortality and complications. Methods: A retrospective review of patients aged 14 years or younger presenting to a single adult L-I and L-II PTC was performed. Patients from 2015–2016 (PRE) were compared with patients from 2018–2019 (POST) for mortality and complications using bivariate analyses. Results: Compared with the PRE cohort, there were less patients in the POST cohort (277 vs 373). Patients in the POST cohort had higher rates of insurance coverage (91.3% vs 78.8%, P < 0.001), self-transportation (7.2% vs 2.7%, P < 0.01), and hospital admission (72.6% and 46.1%, P < 0.001). There was no difference in all complications and mortality (all P > 0.05) between the 2 cohorts. Conclusions: After opening a second L-II PTC within a 2-mile radius, there was an increase in the rate of admissions and self-transportation to the preexisting L-II PTC. Despite a nearly 26% decrease in pediatric trauma volume, there was no difference in length of stay, hospital complications, or mortality.